2006
DOI: 10.1111/j.1460-9568.2006.05025.x
|View full text |Cite
|
Sign up to set email alerts
|

Spatial location is accurately tracked by human auditory sensory memory: evidence from the mismatch negativity

Abstract: The nature of spatial representation in human auditory cortex remains elusive. In particular, although humans can discriminate the locations of sounds as close as 1-10 degrees apart, such resolution has not been shown in auditory cortex of humans or animals. We used the mismatch negativity (MMN) event related brain potential to measure the neural response to spatial change in humans in narrow 10 degree spatial steps. Twelve participants were tested using a dense array EEG setup while watching a silent movie an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
76
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 83 publications
(88 citation statements)
references
References 53 publications
11
76
1
Order By: Relevance
“…As can be seen in Figure 3, the MMN to location deviants had a clear double peak, consistent with previous reports (Tata & Ward, 2005;Deouell et al, 2006). The first peak reached maximum amplitude around 120 ms and the second around 195 ms.…”
Section: Mismatch Negativity (Mmn)supporting
confidence: 80%
See 1 more Smart Citation
“…As can be seen in Figure 3, the MMN to location deviants had a clear double peak, consistent with previous reports (Tata & Ward, 2005;Deouell et al, 2006). The first peak reached maximum amplitude around 120 ms and the second around 195 ms.…”
Section: Mismatch Negativity (Mmn)supporting
confidence: 80%
“…Moreover, the amplitude and latency of the MMN has been shown to be related to the magnitude of deviation along a variety of dimensions (e.g. Tiitinen et al, 1994;Yago et al, 2001;Amenedo & Escera, 2000;Deouell et al, 2006), and can thus provide objective measures of the representation of a specific dimension in sensory memory. This makes the MMN a promising tool for investigating the integrity of sensory processing and prediction in clinical groups (Näätänen, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…5). Parietal and posterior temporal cortices have been shown to be implicated in auditory spatial functions in man (Griffiths et al, 1998;Bushara et al, 1999;Maeder et al, 2001;Weeks et al, 2001;Ducommun et al, 2002;Deouell et al, 2006;Sonnadara et al, 2006;Tardif et al, 2006;De Santis et al, 2007) and nonhuman primate (Stricane et al, 1996;Schlack et al, 2005). Previous studies on ITD processing have shown that left hemisphere responds more specifically to stimuli lateralized in the right hemispace whereas right hemisphere respond to stimuli in the left or right hemispace (Kuwada and Yin, 1983;Caird and Klinke, 1987).…”
Section: Discussionmentioning
confidence: 99%
“…However, human electroencephalography (EEG) in principle allows head movements, and it provides a well studied and reliable electrophysiological marker for auditory spatial processing: the mismatch negativity (MMN) which is elicited by infrequent changes of sound location after repetitive stimulation from the same location (Paavilainen et al, 1989;Schröger and Wolff, 1996;Winkler et al, 1998;Kaiser et al, 2000). EEG and fMRI studies have shown that the MMN to spatial changes is modulated by the extent of spatial deviation and that it might be generated in the planum temporale (Deouell et al, 2006(Deouell et al, , 2007. Possibly, these MMN generators are part of the dorsal wherepathway which has been proposed based on neurophysiological studies in nonhuman primates suggesting that cortical processing of auditory sound localization occurs along a dorsal stream including the caudal parts of the auditory belt, posterior parietal, and dorsal prefrontal cortex (Rauschecker, 1998;Romanski et al, 1999).…”
Section: Introductionmentioning
confidence: 99%